Oxide Nanolayers in Stratified Samples Studied by X-Ray Resonant Raman Scattering at Grazing Incidence - Juan José Leani; Héctor Jorge Sánchez; Carlos Alberto Pérez (Journal of Spectroscopy)
X-ray resonant Raman scattering is applied at grazing incidence conditions with the aim of discriminating and identifying chemical environment of iron in different layers of stratified materials using a low resolution energy dispersive system. The methodology allows for depth studies with nanometric resolution. Nanostratified samples of Fe oxides were studied at the Brazilian synchrotron facility (LNLS) using monochromatic radiation and an EDS setup. The measurements were carried out in grazing incident regime with incident photon energy lower than and close to the Fe-K absorption edge. The result allowed for characterizing oxide nanolayers, not observable with conventional geometries, identifying the oxidation state present in a particular depth of a sample surface with nanometric, or even subnanometric, resolution using a low-resolution system.